Jazz fusion : A Case study of ethno funk by Tophati / Mohd Azirien Ishak - Ishak, Mohd Azirien (Faculty of Business and Management, 2013)
For the past 60 years, jazz has spread to almost every country in the world and has been listened by various people of all ethnic and religious backgrounds. During the 60’s and the 70’s jazz was mainly popular only among the people in the west but nowadays, many people in Asia have embraced jazz and made it as one of their favourite genres in music. Musicians like Mile Davis, John Mclaughlin and Pet Metheny have influenced musicians around Asia to fusejazz music with their local music. Since the 70’s, jazz fusion has grown from lradilionaljazz music and many influential musicians started to fuse jazz music with other genres, notably rock, and rn‘b, When the fusion music style landed in Asia, local musicians slaned to mix jazz with ethnic music for example, Arabic and Indonesian ethnic music‘ Thus, a fusion style akin to the music, the Indonesian guitarist/composer Tohpati was born. Tohpati spécifically mixes contemporary jazz with his ethnic music elements, specifically the Javanese musical element and thus creating music in the genre of contemporary jazz fusion. The purpose of my research project is to study the relationship between melody and harmony in Ethno Funk by Tohpati and lo analyse on the way in which Tohpati fuses elements of ethnic and rock music with jazz harmony in Ethno Funk.